The dynamic relationship between news and social media agendas in the context of information society - Sergidou, Nelly-Maria (My University, 2024)
Greece has been in economic and sociopolitical turmoil since 2009. On the 27th of June 2015, the Greek coalition government led by left-wing SYRIZA announced the July 5th referendum calling citizens to decide whether the EU-proposed economic plan should be adopted or not. The referendums in Greece are rather uncommon and the decision triggered multiple competing narratives regarding the motives behind the referendum. The SYRIZA-led government supported the “No” vote, arguing that a rejection of the EU-proposed economic plan would provide Greece with the leverage to negotiate a better deal with the creditors. On the other side, established elite political forces advocated for the “Yes” vote, voicing concerns that a rejection of the deal would lead Greece to default, exit from the EU, and eventually international isolation. The present research aims to examine the media coverage of the referendum campaign and the sentiments that were expressed on social media, during an extremely short referendum campaign. More specifically, the research goals are: a) to explore the salient issues that emerged in the public debate around the Greek Referendum in the news media using press data to uncover the dominant topics that were put forward by journalists and columnists; b) to explore the salient issues and the sentiments that emerged in the public debate around the Greek Referendum in the social media using Twitter data as a tool to describe the patterns of the daily political discussions about the referendum and the two vote choices. Based on agenda-setting theory and priming theory, the main research question is: Which issues are made most salient in the online Press and on Twitter during the Greek bailout referendum campaign? To address this question, a dataset of newspaper articles and tweets was selected which was analyzed with the use of content and sentiment analysis. The findings of this doctoral research contribute to a nuanced understanding of the intricate interaction between different media types, news content, media agendas, and the formation of public opinion in the digital age. This complexity precludes the identification of a definitive agenda setter or gatekeeper. Notably, the emergence of social media as a formidable force in recent decades has compelled news media to undergo adaptation and formulate novel strategies for agenda regulation and setting. Our findings underscore the inherent unpredictability of media agendas, which cannot be predicted because it depends on many factors. Timeliness, the prevalence of fake accounts manipulating media discussion, and the unique characteristics of each media platform all contribute to the fluidity of agenda construction. In essence, the landscape of media agendas remains elusive, defying straightforward prediction. The mutual influence between news and social media, characterized xviii by constant adaptation and evolution, necessitates an ongoing and systematic exploration of their dynamics. In this context, our study advocates for a continuous examination of media agendas, recognizing the evolving nature of the media landscape. As media landscapes continue to evolve, fostering a society capable of critically evaluating media content becomes indispensable. The role of education emerges as paramount, underscoring the need to equip individuals with the skills to engage with media critically.
Keywords: News media; social media; Referendum Campaigns; Agenda Setting; Priming Theory; Content Analysis; Topic modeling; Greece